1990
DOI: 10.1111/j.1476-5381.1990.tb14080.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological profile of a tachykinin antagonist, spantide, as examined on rat spinal motoneurones

Abstract: 1 The pharmacological profile of a tachykinin antagonist, [D-Arg1, D-Trp7'9, Leu"] substance P (spantide), was studied on motoneurones of the isolated spinal cord of the newborn rat. For this purpose, potentials were recorded from a lumbar ventral root extracellularly and drugs were bath-applied in the presence of tetrodotoxin (TTX). 2 Neurokinin A (NKA), a NK2-receptor selective agonist, induced concentration-dependent depolarizations, which were antagonized by spantide. Analyses of concentration-response cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Since it was known in peripheral tissues that acetyl-Arg6-septide and NKA preferentially act on NK, and NK2 receptors, respectively, the receptor to which NKA and acetyl-Arg6-septide bind as observed in the present study appears to be distinct from NKI, NK2 or NK3 receptor found in peripheral tissues. The existence of this novel type of receptor was suggested previously based on the similar antagonist profile of spantide against the depolarizing responses of motoneurones to NKA and acetyl-Arg6-septide (Yanagisawa & Otsuka, 1990). On the other hand, the significantly lower pA2 of GR71251 against the SP-induced depolarizing responses than against the NKA-and acetyl-Arg6-septide-induced responses may reflect involvement of another type of tachykinin receptor in the SP-induced response.…”
Section: Effects Of Gr71251 On the Dorsal Root-evoked Spinal Reflexesmentioning
confidence: 83%
“…Since it was known in peripheral tissues that acetyl-Arg6-septide and NKA preferentially act on NK, and NK2 receptors, respectively, the receptor to which NKA and acetyl-Arg6-septide bind as observed in the present study appears to be distinct from NKI, NK2 or NK3 receptor found in peripheral tissues. The existence of this novel type of receptor was suggested previously based on the similar antagonist profile of spantide against the depolarizing responses of motoneurones to NKA and acetyl-Arg6-septide (Yanagisawa & Otsuka, 1990). On the other hand, the significantly lower pA2 of GR71251 against the SP-induced depolarizing responses than against the NKA-and acetyl-Arg6-septide-induced responses may reflect involvement of another type of tachykinin receptor in the SP-induced response.…”
Section: Effects Of Gr71251 On the Dorsal Root-evoked Spinal Reflexesmentioning
confidence: 83%
“…Thus a number of selective NK 1 agonists mimic effects of substance P on motoneurons, e.g., substance P methyl ester and [Sar 9 Met(O 2 ) 11 ]substance P, and those effects are blocked by some NK 1 receptor antagonists, i.e., SR-140,333 (52, 365, 726). However, a number of additional NK 1 antagonists are without effect on substance P responses, i.e., (±)-CP-96,345, RP-67580, and GR-82334, or display pharmacological profiles unlike that of the classical NK 1 receptor, i.e., spantide (51,726,1402). Motoneurons may express a distinct isoform of the NK 1 receptor that possesses atypical antagonist binding characteristics (1402).…”
Section: Functional Role Of Trh In Modulating Motoneuronal Excitabilimentioning
confidence: 99%
“…Therefore, it is ap parent that in contrast to tissues rich in the NK1-receptor subtype such as the guinea pig ileum and vas deferens, the NK1-selective antagonist preferentially antagonizes the contractile response to NKA rather than SP in the rabbit iris sphincter muscle. A similar unexpected behavior has been noted in neonatal rat spinal motoneurones (20) and hamster trachea (21) to which NKA and spantide or L 668,169 bind competitively with a high affinity. Ueda et al (11) have reported that in the isolated rabbit iris sphin cter preparation, the contractile response to SP is more prolonged not only in the time to reach the maximal response but also in washout time required to restore the original level as compared to the case of the NKA response, and yet the contractile response declines grad ually upon repetitive application of SP in contrast to no development of such tachyphylaxis to NKA.…”
Section: Resultsmentioning
confidence: 78%